Effect of cranberry extract on the adhesive capacity of dental plaque in the teeth of 10-year-old children from the Horacio Morales Delgado school. Arequipa-Peru 2016. - Andy Paucar Rodriguez (2020)
OBJECTIVES: The objectives of this research were to determine the effect of the cranberry on the adhesive capacity of dental plaque in the children of the Horacio Morales school in the city of Arequipa, Peru. METHODOLOGY AND METHODS: For this research, cranberry extract was tested on 17 10-year-old children at the Horacio Morales Delgado School in Arequipa, Peru. This research lasted two days, the first day we proceeded to brush teeth to children who remained for an hour without food intake, at the end of which they were taken the dental plaque index (control group). On the second day we also proceeded to brush the children’s teeth and immediately applied the Cranberry extract as a mouthwash, after an hour without having ingested any food or drink, we took the dental plaque index. RESULTS: The results obtained from the evaluation were measured with the dental plaque index which has values of 0, 1, 2, 3; depending on how much plaque is in the dental piece (Silness and Loe plaque index). The average plaque index in teeth of children not treated with Cranberry extract and only brushed with prophylactic paste was 1.18. The average plaque index in teeth of children treated with Cranberry extract was 0.18. The results show a very significant contrast in the two days of the experiment, reaching the conclusion that using Cranberry extract significantly reduces the level of dental plaque adhered to the enamel of the teeth.